Dry particle composition and anti-skid and anti-fouling glazed ceramic tile and preparation method thereof

By using dry-grain compositions with specific chemical composition and particle size distribution, the existing anti-slip ceramic tiles have been solved, with low bonding strength, poor wear resistance and insufficient anti-fouling ability of the existing anti-slip ceramic tiles, and the effect of the ceramic tiles is delicate, better anti-slip and anti-fouling properties, and stronger wear resistance.

CN119330593BActive Publication Date: 2025-04-04GUANGDONG NEWPEARL CERAMIC GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411886002.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing anti-slip ceramic tiles are coated with polymer anti-slip liquid on the surface and have low bond strength, poor wear resistance, insufficient pollution resistance, and high-temperature particles can easily lead to glaze defects.

Method used

Dry particle compositions with specific chemical composition and particle size distribution, including dry particle A and dry particle B, are used to define their weight ratio and particle size distribution, so that the degree of melting of dry particle B is higher than that of dry particle A, forming a suitable concave and convex three-dimensional structure, improving slip resistance and stain resistance, and enhancing the wear resistance of ceramic tiles.

Benefits of technology

It achieves the delicate feel of ceramic tiles, better anti-slip and stain resistance, and stronger bonding with glaze surface, while ensuring the wear resistance of ceramic tiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330593B_ABST
    Figure CN119330593B_ABST
Patent Text Reader

Abstract

The present application provides a dry particle composition and an anti-skid and anti-fouling glazed ceramic tile and a preparation method thereof, belonging to the field of ceramic technology. The present application selects dry particles A and B with specific chemical composition formulas and specific particle size distributions for compounding, and limits the weight ratio of the two to an appropriate range, so that the height difference of the concave-convex three-dimensional structure formed by them on the ceramic surface is more appropriate, the roughness is lower, the anti-skid and anti-fouling properties are better, the feel is more delicate, and the bonding force with the ceramic glaze is stronger, while also ensuring that the obtained ceramic has good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of ceramic technology, and in particular to a dry particle composition and an anti-slip and anti-fouling glazed ceramic tile and a preparation method thereof. Background Art

[0002] At present, anti-slip ceramic tiles cover a variety of technical paths to achieve anti-slip. Among them, the technical principle of designing anti-slip glaze is mainly based on the concave-convex surface structure. Through the addition of polymer anti-slip liquid, in-situ crystallization or the addition of high-temperature particles and other technologies, a series of uneven surface structures are formed on the ceramic surface, which effectively increases the surface roughness, thereby increasing the friction of the contact surface and achieving an anti-slip effect. However, when the polymer anti-slip liquid is applied to the surface of ceramic tiles, the bonding strength between the polymer layer and the surface of the ceramic tiles is low after drying, and it is easy to fall off. In addition, the wear resistance of the polymer layer itself is poor, and it is easy to be scratched and worn, resulting in a decrease in surface gloss. In addition, the pits formed by the corrosion of acidic substances in the polymer anti-slip liquid also have the problem of poor anti-fouling ability. For in-situ crystallization, the rapid firing cycle of building ceramics makes it difficult to precipitate suitable crystal types on the surface of ceramic tiles, and the distribution of crystals is uneven, making it difficult to achieve a good anti-slip effect. Adding high-temperature particles is a simple and convenient way to improve the anti-slip ability of ceramic tiles, but it often encounters the problem of improved anti-slip ability but poor anti-fouling ability. The addition of high-temperature dry particles will also cause glaze defects, because the addition of high-temperature dry particles causes the physical and chemical properties of the basic glaze to change, such as the amount of glass phase produced in the high-temperature stage and the temperature of the liquid phase. This will cause the degree of melting of the glaze to decrease during the firing process, thereby causing glaze defects.

[0003] Applying dry particles is one of the important ways to achieve the anti-slip function of building ceramics. When anti-slip dry particles are attached to the surface of ceramic tiles, they often feel rough and are easy to hide dirt due to unreasonable selection of dry particle grading, chemical composition, and addition amount. Because there are gaps between the anti-slip dry particles, dirt is easily stuck at the bottom of the gaps between the dry particles after falling, and it is difficult to clean the bottom of the gaps, resulting in the phenomenon of dirt being stuck and hidden. Summary of the invention

[0004] Based on the defects of the prior art, the purpose of the present application is to provide a dry particle composition and an anti-slip and anti-fouling glazed ceramic tile and a preparation method thereof, so that the ceramic tile formed by applying the dry particles has a delicate feel and has excellent anti-slip and stain resistance.

[0005] In order to achieve the above-mentioned object, in a first aspect, the present application provides a dry particle composition, comprising dry particles A and dry particles B, wherein the weight ratio of the dry particles A to the dry particles B is (5-50): (50-95);

[0006] The dry particles A contain the following chemical components in percentage by weight: 50% to 58% silicon dioxide, 18% to 23% aluminum oxide, 0.10% to 0.45% iron oxide, 0.10% to 0.45% titanium oxide, 10% to 14% calcium oxide, 0.5% to 1.5% magnesium oxide, 3.5% to 5% potassium oxide, 2.5% to 5% sodium oxide, 3% to 5% zinc oxide, and the rest is loss on ignition; the particle size distribution of the dry particles A satisfies: based on the total weight of the dry particles A, 80-100 mesh particles account for 2% to 15%, 100-160 mesh particles account for 22%~30%, 160~220 mesh particles account for 25%~36%, and particles above 220 mesh account for 19%~55%; the dry particles B contain the following chemical components in percentage by weight: silicon dioxide 40%~45%, aluminum oxide 20%~23%, ferric oxide 0.10~0.45%, titanium oxide 0.10~0.45%, calcium oxide 1.5%~5%, magnesium oxide 0.5%~3%, potassium oxide 1%~2.5%, sodium oxide 3%~6%, strontium oxide 3%~6%, barium oxide 8%~16%, zinc oxide 3%~6%, and the rest is loss on ignition;

[0007] The dry particles B also meet the following requirements: 10 =5~10μm, d 50 =10~30μm, d 90 =40~70μm.

[0008] The dry particle composition comprises dry particles A and dry particles B. By limiting the dry particles A and B to adopt specific chemical composition formulas, specific particle size distributions and a weight ratio between the two within a specific range, the melting degree of the dry particles B is higher than that of the dry particles A, the overall particle size of the dry particles A is coarser than that of the dry particles B, and the amount of dry particles A added is less than that of the dry particles B. In this way, the height difference of the concave-convex three-dimensional structure formed on the surface of the ceramic is more suitable, the roughness is lower, the anti-slip and anti-fouling properties are better, the hand feel is more delicate, the bonding force with the ceramic glaze is stronger, and at the same time, the ceramic is ensured to have good wear resistance.

[0009] The final comprehensive physical and chemical properties of ceramic tiles, including their overall anti-slip properties, excellent anti-fouling ability, delicate feel and just the right surface roughness, these key attributes cannot be achieved by a single factor, but are shaped by multiple complex and delicate components.

[0010] The particle size of the combined dry particles A and B, the chemical composition contained in the two, and the weight ratio of the two also have a decisive influence on the final performance of the glaze. The combination of the dry particles A and B in this patent can achieve the final glaze effect. If you only want to improve the anti-slip performance, you can directly choose high-temperature dry particles with a melting temperature of more than 1165°C. This is very simple in the field of materials, but too high a melting temperature will affect the high-temperature bonding ability of the dry particles and antique glazes, that is, the high-temperature dry particles are easy to fall off, and the wear resistance of the glazed tiles will decrease. This patent adjusts the chemical composition and particle size of the dry particles, that is, through the reasonable combination of large-particle-size dry particles A and small-particle-size dry particles B, the dry particles A with a higher initial melting point and the dry particles B with a lower initial melting point are matched with each other. The regulation of the initial melting point mainly considers the content of silicon dioxide and aluminum oxide. As network formers, they determine the initial melting temperature of the dry particles. Other metal oxides in the formula, such as calcium oxide, magnesium oxide, potassium oxide, sodium oxide, zinc oxide, strontium oxide (if any), barium oxide (if any), etc., are all network destroyers. The total content of alkali metal oxides is lower than that of alkaline earth metal oxides. This is to control the melting of the dry particles at a higher temperature. This is also the idea of ​​the entire formula design adjustment of dry particles A and dry particles B. The content, type and addition amount of alkali metal oxides and alkaline earth metal oxides determine the melting temperature range of the dry particles, but the size of the particles is different, the specific surface area is different, and the sintering activity is different. The particle size, chemical composition and addition amount jointly affect the melting degree of the dry particles. After high-temperature firing, the presence of coarse and fine glaze dry particles can form an uneven surface structure on the glaze surface. This roughness can prove that the presence of particles changes the surface roughness.

[0011] The specific silicon dioxide content and aluminum oxide content of dry particles A and dry particles B are selected to ensure that the initial melting points of the two are high, and the initial melting point of dry particles A is higher than that of dry particles B; dry particles A and dry particles B respectively contain potassium oxide and sodium oxide alkali metal oxides that can produce liquid phases in a lower temperature range, but the amount of liquid phase produced also needs to be controlled, otherwise high-temperature dry particles will produce more liquid phases at a lower temperature, resulting in excessive melting of the size of the dry particles. At the same time, in order to ensure that the dry particles can be well combined with the antique glaze, there are very few pores or no pores at the joints of the dry particles, which can ensure the anti-fouling performance. Therefore, alkaline earth metal oxides that can produce liquid phases in a high temperature range are selected, such as barium oxide, calcium oxide, magnesium oxide, zinc oxide, strontium oxide (if any), barium oxide (if any), etc. The mutual coordination of various components can achieve the mutual consideration of the anti-fouling, anti-slip and wear-resistant properties of the glaze.

[0012] In addition, in order to ensure that dry particles B have a higher initial melting point, the total content of silicon dioxide and aluminum oxide is about 60%~68%. Considering that sodium oxide and potassium oxide are compared with calcium oxide, strontium oxide, barium oxide, zinc oxide, etc., they are metal oxides that can promote the production of liquid phase in dry particles at relatively low temperatures. The liquid phase produced too early or too much in the low temperature stage is not conducive to controlling the size of dry particles. At the same time, it is necessary to ensure that a certain liquid phase can be produced in the high temperature stage to promote the good combination of dry particles with antique protective glaze. Therefore, strontium oxide, barium oxide, and zinc oxide in the high temperature stage are selected as the main alkaline earth metal oxides to form a low eutectic point and promote the production of liquid phase. The production of low eutectic points involves the type and content of oxides, which is why specific types of metal oxides need to be combined together, and certain metal oxides cannot be selected at will.

[0013] It is worth noting that any slight change among these four, whether it is a fine-tuning of the chemical composition of the antique protective glaze, or a change in the particle size, chemical composition or addition amount of dry particles A and B, may cause a significant change in the overall effect of the glaze, like a butterfly effect. This is a highly sensitive and interdependent relationship.

[0014] Preferably, the dry particles A contain the following chemical components in percentage by weight: 50% to 55% silicon dioxide, 18% to 22% aluminum oxide, 0.10% to 0.35% iron oxide, 0.10% to 0.35% titanium oxide, 12% to 14% calcium oxide, 0.5% to 1% magnesium oxide, 3.5% to 4.5% potassium oxide, 2.5% to 4.5% sodium oxide, 3% to 4.5% zinc oxide, and the rest is ignition reduction, so that the ceramic tile has a delicate feel and good stain resistance and wear resistance, while having better anti-slip properties.

[0015] Preferably, the dry particles B contain the following chemical components in percentage by weight: 40% to 44% silicon dioxide, 20% to 22% aluminum oxide, 0.1% to 0.35% iron oxide, 0.1% to 0.35% titanium oxide, 1.5% to 2.5% calcium oxide, 0.5% to 2% magnesium oxide, 1% to 2.5% potassium oxide, 4% to 5.5% sodium oxide, 4% to 5.5% strontium oxide, 10% to 16% barium oxide, 3% to 6% zinc oxide, and the rest is ignition reduction, so that the ceramic tile has a delicate feel and good stain resistance and wear resistance, while having better anti-slip properties.

[0016] Preferably, the particle size distribution of the dry particles A satisfies: based on the total weight of the dry particles A, 80-100 mesh particles account for 2%-4.5%, 100-160 mesh particles account for 22%-26%, 160-220 mesh particles account for 25%-34%, and particles above 220 mesh account for 25%-40%, so that the ceramic tile has a delicate feel and good stain resistance and wear resistance, while having better anti-slip properties.

[0017] Preferably, the dry particles B satisfy: 10 =5~8μm, d 50 =15~25μm, d 90 =45~55μm, so that the ceramic tiles have a delicate feel and good stain and wear resistance, while also having better anti-slip properties.

[0018] The weight ratio of the dry particles A to the dry particles B is (5-50): (50-95). Preferably, the weight ratio of the dry particles A to the dry particles B is (10-30): (70-90), so that the ceramic tile has excellent anti-slip and anti-fouling capabilities.

[0019] In a second aspect, the present application provides a ceramic tile, comprising a body layer, a base glaze layer, a pattern layer, an antique protective glaze layer, and a dry particle layer formed by the dry particle composition stacked in sequence.

[0020] As an example, the antique protective glaze layer contains the following chemical components in weight percentage: 46% to 52% silicon dioxide, 17% to 22% aluminum oxide, 0.1% to 0.4% iron oxide, 0.1% to 0.3% titanium oxide, 10% to 16% calcium oxide, 1% to 4% magnesium oxide, 0.3% to 3% potassium oxide, 1% to 5% sodium oxide, 0% to 5% barium oxide, 2% to 6% zinc oxide, and the rest is ignition reduction. When the antique protective glaze layer adopts this specific chemical composition formula, the resulting ceramic tile has excellent antique effect and protective effect.

[0021] In addition to the above chemical composition formula, the antique protective glaze layer may also adopt other antique protective glaze chemical composition formulas. For example, in some embodiments, the antique protective glaze layer contains the following chemical components in weight percentage: 53% silicon dioxide, 18% aluminum oxide, 0.5% iron oxide, 0.5% titanium oxide, 9% calcium oxide, 5% magnesium oxide, 4% potassium oxide, 4% sodium oxide, 6% zinc oxide, and the rest is ignition reduction. When the antique protective glaze layer adopts this specific chemical composition formula, the resulting ceramic tile has excellent antique effect and protective effect.

[0022] In a third aspect, the present application provides a method for preparing a ceramic tile, comprising the following steps: drying after pressing the brick blank, applying a base glaze, inkjet printing, baking, applying an antique protective glaze, spraying a particle suspension, firing, and grinding edges to obtain a ceramic tile;

[0023] The dry particle suspension comprises the dry particle composition.

[0024] Preferably, the dry particle suspension further comprises a suspension, wherein the dry particle composition accounts for 20 wt.% to 60 wt.% of the dry particle suspension, the suspension accounts for 40 wt.% to 80 wt.% of the dry particle suspension, and the specific gravity of the dry particle suspension is 1.0 to 1.35 g / mL.

[0025] Preferably, the suspension contains a suspending agent. Exemplarily, the suspending agent includes at least one of carboxymethyl cellulose, ethylene glycol, polyvinyl alcohol, and glycerol.

[0026] Preferably, the suspending agent accounts for 20 wt.% to 45 wt.% of the weight of the suspension. Preferably, the suspension further comprises a solvent, and the solvent is water.

[0027] Preferably, the spray-dried particle suspension satisfies: the spraying amount of the dry particle suspension is 50-150 g / m 2 , spraying pressure is 4~6.5 MPa, nozzle diameter is 0.52 mm, and there are 2~4 spray guns.

[0028] Preferably, the baking temperature is 150-250° C. and the baking time is 0.5-5 min to avoid the high ink content of the ceramic ink affecting the glaze spraying effect and causing defects.

[0029] Preferably, the method of applying the antique protective glaze is spraying glaze, and the following conditions are met: the specific gravity of the antique protective glaze slurry is 1.20-1.35 g / mL, and the spraying amount is 100-200 g / m 2 , spraying pressure is 4~6.5 MPa, nozzle diameter is 0.52 mm, and there are 2~4 spray guns.

[0030] Preferably, the sintering temperature is 1150-1165° C., and the sintering time is 35-45 min.

[0031] Preferably, the drying temperature after pressing the bricks and before applying the base glaze is 150-200 °C.

[0032] Compared with the prior art, the beneficial effects of this application are:

[0033] (1) The present application selects dry particles A and B with specific chemical composition formulas and specific particle size distributions for compounding, and limits the weight ratio of the two to an appropriate range, so that the height difference of the concave-convex three-dimensional structure formed by them on the ceramic surface is more appropriate, the roughness is lower, the anti-slip and anti-fouling properties are better, the hand feel is more delicate, the bonding force with the ceramic glaze is stronger, and at the same time, it ensures that the obtained ceramic has good wear resistance.

[0034] (2) Compared with the conventional method of adding anti-skid dry particles to the glaze slurry to form a concave-convex structure on the ceramic surface, the present application uses a dry particle composition to form a dry particle layer on the surface of the antique protective glaze, so that a smaller mass of high-temperature dry particles can be used to achieve a better anti-skid effect and maintain excellent anti-fouling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a process flow chart for preparing ceramic tiles of Example 1.

[0036] Figure 2 The surface microstructure of the antique glazed ceramic tile prepared by the antique protective glaze of Example 1 (the preparation method is different from that of Example 1 only in that the antique protective glaze is sprayed before direct firing, without spraying the dry particle suspension).

[0037] Figure 3 This is the surface microstructure of the anti-slip and anti-fouling antique glazed tile prepared in Example 1.

[0038] Figure 4 This is the surface microstructure of the anti-slip and anti-fouling antique glazed tile prepared in Example 2.

[0039] Figure 5 It is a schematic diagram of the cross-sectional structure of the anti-slip and anti-fouling ceramic tile of the present invention (the antique glaze layer is the antique protective glaze layer). DETAILED DESCRIPTION

[0040] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of this application are all commonly used ordinary reagents and instruments unless otherwise specified. In the present application, the technical features described in an open manner include closed technical schemes composed of the listed features, and also include open technical schemes containing the listed features.

[0041] Example 1

[0042] This embodiment provides a ceramic tile, which includes a green body layer, a base glaze layer, a pattern layer, a protective glaze layer and a dry particle layer formed by a dry particle composition stacked in sequence;

[0043] The dry granule composition comprises dry granules A and dry granules B, and the weight ratio of dry granules A to dry granules B is 30:70;

[0044] The dry particles A contain the following chemical components in percentage by weight: 50% silicon dioxide, 22% aluminum oxide, 0.35% iron oxide, 0.35% titanium oxide, 12% calcium oxide, 1% magnesium oxide, 4.5% potassium oxide, 2.5% sodium oxide, 4.5% zinc oxide, and the rest is loss on ignition; and the particle size distribution of the dry particles A satisfies: based on the total weight of the dry particles A, particles of 80-100 meshes account for 4%, particles of 100-160 meshes account for 30%, particles of 160-220 meshes account for 36%, and particles of more than 220 meshes account for 30%;

[0045] The dry granules B contain the following chemical components in percentage by weight: silicon dioxide 44%, aluminum oxide 20%, iron oxide 0.1%, titanium oxide 0.1%, calcium oxide 1.5%, magnesium oxide 0.5%, potassium oxide 1%, sodium oxide 5.5%, strontium oxide 5.5%, barium oxide 10%, zinc oxide 6%, and the remainder is loss on ignition; and the dry granules B also meet the following requirements: 10 =8μm, d 50 =25μm, d 90 =45μm;

[0046] The antique protective glaze layer contains the following chemical components in weight percentage: silicon dioxide 46%, aluminum oxide 22%, iron oxide 0.4%, titanium oxide 0.3%, calcium oxide 14%, magnesium oxide 1%, potassium oxide 3%, sodium oxide 1%, barium oxide 5%, zinc oxide 2%, and the rest is loss on ignition.

[0047] The preparation method of the ceramic tile of this embodiment refers to Figure 1 , including the following steps:

[0048] The dry particle composition is added to the suspension and stirred for 5 minutes to obtain a dry particle suspension with a specific gravity controlled at 1.05 g / mL, wherein the suspension is prepared by mixing and dispersing water and a suspending agent, polyvinyl alcohol, and the content of the suspending agent in the suspension is 30wt.%;

[0049] The brick blank is pressed, dried for the first time at 150°C, coated with a base glaze, inkjet printed, baked at 250°C, sprayed with an antique protective glaze, sprayed with the above-mentioned dry particle suspension, fired at 1150°C for 40min, and edged to obtain a ceramic tile;

[0050] Among them, the spraying of antique protective glaze meets the following requirements: the specific gravity of the antique protective glaze slurry is 1.3g / mL, and the spraying amount is 100g / m 2 , spraying pressure is 4 MPa, nozzle diameter is 0.52 mm, and 2 spray guns;

[0051] The spraying amount of dry particle suspension is 50g / m 2 , spraying pressure is 6.5 MPa, nozzle diameter is 0.52 mm, and there are 2 spray guns.

[0052] Example 2

[0053] This embodiment provides a ceramic tile, which differs from Embodiment 1 as follows: the chemical composition formula of dry particles A is different. In this embodiment, dry particles A contain the following chemical components in percentage by weight: 55% silicon dioxide, 18% aluminum oxide, 0.1% iron oxide, 0.1% titanium oxide, 14% calcium oxide, 0.5% magnesium oxide, 3.5% potassium oxide, 4.5% sodium oxide, 3% zinc oxide, and the rest is loss on ignition.

[0054] Example 3

[0055] This embodiment provides a ceramic tile, which differs from Embodiment 1 as follows: the chemical composition formula of dry particles A is different. In this embodiment, dry particles A contain the following chemical components in percentage by weight: 56% silicon dioxide, 23% aluminum oxide, 0.4% iron oxide, 0.35% titanium oxide, 10% calcium oxide, 0.5% magnesium oxide, 4.25% potassium oxide, 2.5% sodium oxide, 2.5% zinc oxide, and the rest is loss on ignition.

[0056] Example 4

[0057] This embodiment provides a ceramic tile, which differs from Embodiment 1 as follows: the chemical composition formula of dry particles A is different. In this embodiment, dry particles A contain the following chemical components in percentage by weight: 56% silicon dioxide, 18% aluminum oxide, 0.35% iron oxide, 0.35% titanium oxide, 10% calcium oxide, 0.5% magnesium oxide, 3.5% potassium oxide, 5% sodium oxide, 5% zinc oxide, and the rest is loss on ignition.

[0058] Example 5

[0059] This embodiment provides a ceramic tile, which differs from Embodiment 1 as follows: the chemical composition formula of dry particles B is different. In this embodiment, dry particles B contain the following chemical components in percentage by weight: 40% silicon dioxide, 22% aluminum oxide, 0.35% iron oxide, 0.35% titanium oxide, 2.5% calcium oxide, 2% magnesium oxide, 2.5% potassium oxide, 4% sodium oxide, 4% strontium oxide, 16% barium oxide, 3% zinc oxide, and the rest is loss on ignition.

[0060] Example 6

[0061] This embodiment provides a ceramic tile, which differs from Embodiment 1 as follows: the chemical composition formula of dry particles B is different. In this embodiment, dry particles B contain the following chemical components in percentage by weight: 45% silicon dioxide, 20% aluminum oxide, 0.3% iron oxide, 0.3% titanium oxide, 5% calcium oxide, 0.5% magnesium oxide, 2.5% potassium oxide, 6% sodium oxide, 6% strontium oxide, 8% barium oxide, 3% zinc oxide, and the rest is loss on ignition.

[0062] Example 7

[0063] This embodiment provides a ceramic tile, which differs from Embodiment 3 as follows: the chemical composition formula of dry particles B is different. In this embodiment, dry particles B contain the following chemical components in percentage by weight: 40% silicon dioxide, 23% aluminum oxide, 0.15% iron oxide, 0.3% titanium oxide, 5% calcium oxide, 0.5% magnesium oxide, 2.5% potassium oxide, 3% sodium oxide, 6% strontium oxide, 15% barium oxide, 3% zinc oxide, and the rest is loss on ignition.

[0064] Example 8

[0065] This embodiment provides a ceramic tile, which is different from Embodiment 1 as follows: the particle size distribution of dry particles A is different. The particle size distribution of dry particles A in this embodiment satisfies: based on the total weight of the dry particles A, particles of 80-100 mesh account for 15%, particles of 100-160 mesh account for 22%, particles of 160-220 mesh account for 30%, and particles of 220 mesh and above account for 33%.

[0066] Example 9

[0067] This embodiment provides a ceramic tile, which is different from Embodiment 1 as follows: the particle size distribution of dry particles A is different. The particle size distribution of dry particles A in this embodiment satisfies: based on the total weight of the dry particles A, particles of 80-100 mesh account for 3%, particles of 100-160 mesh account for 28%, particles of 160-220 mesh account for 29%, and particles of 220 mesh and above account for 40%.

[0068] Example 10

[0069] This embodiment provides a ceramic tile, which is different from Embodiment 1 as follows: the particle size distribution of dry particles A is different. In this embodiment, the particle size distribution of dry particles A satisfies: 80-100 mesh particles account for 2%, 100-160 mesh particles account for 22%, 160-220 mesh particles account for 28%, and particles above 220 mesh account for 48%.

[0070] Embodiment 11

[0071] This embodiment provides a ceramic tile, which is different from the embodiment 1 as follows: the particle size distribution of the dry particles B is different. In this embodiment, the particle size distribution of the dry particles B satisfies: d 10 =5μm, d 50 =15μm, d 90 =55μm.

[0072] Example 12

[0073] This embodiment provides a ceramic tile, which is different from the embodiment 1 as follows: the particle size distribution of the dry particles B is different. In this embodiment, the particle size distribution of the dry particles B satisfies: d 10=7 μm, d 50 =30μm, d 90 =65μm.

[0074] Example 13

[0075] This embodiment provides a ceramic tile, which is different from the embodiment 1 as follows: the particle size distribution of the dry particles B is different. In this embodiment, the particle size distribution of the dry particles B satisfies: d 10 =9μm, d 50 =14μm, d 90 =70μm.

[0076] Embodiment 14

[0077] This embodiment provides a ceramic tile, which differs from Embodiment 1 in that the weight ratio of dry particles A to dry particles B is 5:95.

[0078] Embodiment 15

[0079] This embodiment provides a ceramic tile, which differs from Embodiment 1 in that the weight ratio of dry particles A to dry particles B is 50:50.

[0080] Comparative Example 1

[0081] This comparative example provides a ceramic tile, which differs from Example 1 as follows: the chemical composition formula of dry particles A is different. In this example, dry particles A contain the following chemical components in percentage by weight: 48% silicon dioxide, 25% aluminum oxide, 0.2% iron oxide, 0.2% titanium oxide, 10% calcium oxide, 2% magnesium oxide, 4% potassium oxide, 3% sodium oxide, 5% zinc oxide, and the rest is loss on ignition.

[0082] Comparative Example 2

[0083] This comparative example provides a ceramic tile, which differs from Example 1 as follows: the chemical composition formula of dry particles B is different. In this example, dry particles B contain the following chemical components in percentage by weight: 59% silicon dioxide, 20% aluminum oxide, 0.2% iron oxide, 0.2% titanium oxide, 8% calcium oxide, 1.6% magnesium oxide, 6% potassium oxide, 2% sodium oxide, 3% zinc oxide, and the rest is loss on ignition.

[0084] Comparative Example 3

[0085] This comparative example provides a ceramic tile, which is different from Example 1 as follows: the particle size distribution of dry particles A is different. The particle size distribution of dry particles A in this example satisfies: 80-100 mesh particles account for 20%, 100-160 mesh particles account for 20%, 160-220 mesh particles account for 50%, and particles above 220 mesh account for 10%.

[0086] Comparative Example 4

[0087] This comparative example provides a ceramic tile, which is different from Example 1 as follows: the particle size distribution of dry particles B is different, and the particle size distribution of dry particles B is different, and B satisfies: d 10 =20μm, d 50 =40μm, d 90 =80μm.

[0088] Comparative Example 5

[0089] This comparative example provides a ceramic tile, which differs from Example 1 as follows: the formula of dry particles A in this example is the same as that of dry particles B in Example 1.

[0090] Comparative Example 6

[0091] This comparative example provides a ceramic tile, which differs from Example 1 as follows: the formula of dry particles B in this example is the same as that of dry particles A in Example 1.

[0092] Comparative Example 7

[0093] This comparative example provides a ceramic tile, which is different from Example 1 as follows: the particle size distribution of dry particles A is different. The particle size distribution of dry particles A in this example satisfies: 80-100 mesh particles account for 20%, 100-160 mesh particles account for 40%, 160-220 mesh particles account for 35%, and particles above 220 mesh account for 5%.

[0094] Comparative Example 8

[0095] This comparative example provides a ceramic tile, which is different from Example 1 as follows: the particle size distribution of dry particles B is different, and the particle size distribution of dry particles B is different, and B satisfies: d 10 =2μm, d 50 =35μm, d 90 =75μm.

[0096] Comparative Example 9

[0097] This comparative example provides a ceramic tile, which differs from Example 1 as follows: the formula of the dry particles B in this example is changed, and it contains the following chemical components in percentage by weight: 52% silicon dioxide, 25% aluminum oxide, 0.1% iron oxide, 0.1% titanium oxide, 1.5% calcium oxide, 0.5% magnesium oxide, 2.5% potassium oxide, 3% sodium oxide, 3.5% strontium oxide, 5% barium oxide, 2% zinc oxide, and the rest is loss on ignition.

[0098] Comparative Example 10

[0099] This comparative example provides a ceramic tile, which differs from Example 1 as follows: in this example, the zinc oxide in the formula of dry particles B is replaced by an equal amount of boron oxide, and the rest remains unchanged.

[0100] Comparative Example 11

[0101] This comparative example provides a ceramic tile, which differs from Example 1 as follows: in this example, the weight ratio of dry particles A to dry particles B is 60:40, and the others remain unchanged.

[0102] The ceramic tiles obtained from the above embodiments and comparative examples were subjected to the following performance tests:

[0103] Anti-slip property: The anti-slip value is determined according to the test experimental value of Appendix B-Pendulum anti-slip value test method of GB / T 37798-2019 "Evaluation of Anti-slip Performance Grade of Ceramic Tiles".

[0104] Pollution resistance: GB / T 3810.14-2016 "Test methods for ceramic tiles Part 14: Determination of pollution resistance" is used to test the pollution resistance level;

[0105] Wear resistance: GB / T 3810.14-2016 "Test methods for ceramic tiles Part 7: Determination of surface wear resistance of glazed tiles" is used to test the pollution resistance level;

[0106] Feel: The same experimenter conducts the test and touches the sample with his hand to determine whether the feel is fine or rough.

[0107] Surface roughness: Use a surface roughness profiler to characterize the surface roughness. Use two representative parameters, namely, the profile arithmetic mean deviation Ra and the ten-point height of micro-roughness Rz, to evaluate the surface quality and finally obtain the required surface roughness.

[0108] The test results are shown in Table 1.

[0109] Table 1

[0110]

[0111] It can be seen from the above data that the ceramic tiles obtained in each embodiment of the present application have a delicate feel and excellent anti-slip, stain resistance and wear resistance, among which the anti-slip value is above 30, the stain resistance level is above level 5, and the wear resistance level is level 4.

[0112] In Comparative Example 1, the dry particles A adopt a chemical composition formula with a higher initial melting point, resulting in a rough feel of the antique glaze;

[0113] In Comparative Example 2, the dry particles B adopt a chemical composition formula with a higher initial melting point, resulting in a rough feel of the antique glaze;

[0114] In comparative example 3, the particle size distribution of dry particles A is relatively coarse, resulting in a rough feel of the antique glaze;

[0115] The particle size distribution of the dry particles B in Comparative Example 4 is relatively coarse, resulting in a rough feel of the antique glaze.

[0116] In Comparative Example 5, the chemical composition formula of dry particles A is changed to be the same as that of dry particles B in Example 1, so that the contents of silicon oxide and aluminum oxide in dry particles A are reduced, the initial melting temperature is lower, and the combined dry particles melt prematurely, which affects the melting effect of the dry particles and the basic antique protective glaze, resulting in a decrease in the anti-slip performance of the ceramic tile glaze;

[0117] Similarly, the chemical composition formula of dry particles B in comparative example 6 was changed to be the same as that of dry particles A in example 1, so that the content of silicon oxide and aluminum oxide in dry particles B increased, and the melting degree of the combined dry particles decreased, which affected the melting effect of the dry particles and the basic antique protective glaze, resulting in a rough feel of the ceramic tile glaze. The particle size distribution of dry particles A in comparative example 7 was coarse, resulting in a rough feel of the antique glaze. At the same time, because the particles were too large, the melting degree of the glaze was poor, and the bonding strength between the dry particles and the basic glaze was poor, resulting in reduced wear resistance;

[0118] The particle size distribution of the dry particles B in Comparative Example 8 is relatively coarse, resulting in a rough feel of the antique glaze.

[0119] In Comparative Example 9, the total content of silicon dioxide and aluminum oxide in the dry particles B reaches 77%, and the content of alkali metal oxides and alkaline earth metal oxides is reduced. The dry particles have poor high-temperature melting performance and are more able to maintain the original particle size, but also cause the glaze surface to be rougher. In addition, the degree of bonding between the dry particles and the antique protective glaze is affected, and gaps are easily present at the junction of the glaze and the particles, resulting in a decrease in anti-fouling ability.

[0120] In Comparative Example 10, the zinc oxide in the dry particles B is replaced by boron oxide. Boric oxide is a metal oxide that can produce a liquid phase at a relatively low temperature, which will reduce the melting temperature and the initial melting temperature of the dry particles, resulting in premature melting of the dry particles and a delicate glaze surface, but also reducing the anti-slip ability of the glaze surface.

[0121] In Comparative Example 11, too much dry particles A are added, and more high-temperature dry particles are accumulated on the antique glaze surface after firing. The presence of high-temperature dry particles will also hinder the high-temperature melting of the antique glaze, and the flow of liquid is blocked by the high-temperature dry particles. The presence of too many dry particles A on the glaze surface improves the anti-slip ability, but also reduces the pollution resistance. Moreover, too many high-temperature dry particles require more liquid to combine with the dry particles. When the antique glaze remains unchanged, the area of ​​each dry particle combined with the antique glaze decreases, which leads to reduced wear resistance of the glaze and easy pullout of the dry particles.

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A dry granular composition, characterized in that: Comprising dry particles A and dry particles B, wherein the weight ratio of the dry particles A to the dry particles B is (5-50): (50-95); The dry particles A contain the following chemical components in percentage by weight: 50% to 58% silicon dioxide, 18% to 23% aluminum oxide, 0.10% to 0.45% iron oxide, 0.10% to 0.45% titanium oxide, 10% to 14% calcium oxide, 0.5% to 1.5% magnesium oxide, 3.5% to 5% potassium oxide, 2.5% to 5% sodium oxide, 3% to 5% zinc oxide, and the rest is loss on ignition; The particle size distribution of the dry particles A satisfies: based on the total weight of the dry particles A, particles with mesh sizes of 80 to 100 account for 2% to 15%, particles with mesh sizes of 100 to 160 account for 22% to 30%, particles with mesh sizes of 160 to 220 account for 25% to 36%, and particles with mesh sizes of more than 220 account for 19% to 48%; The dry particles B contain the following chemical components in percentage by weight: 40% to 45% silicon dioxide, 20% to 23% aluminum oxide, 0.10% to 0.45% iron oxide, 0.10% to 0.45% titanium oxide, 1.5% to 5% calcium oxide, 0.5% to 3% magnesium oxide, 1% to 2.5% potassium oxide, 3% to 6% sodium oxide, 3% to 6% strontium oxide, 8% to 16% barium oxide, 3% to 6% zinc oxide, and the rest is loss on ignition; The dry particles B also meet the following requirements: 10 =5~10μm, d 50 =10~30μm, d 90 =40~70μm.

2. The dry granular composition according to claim 1, characterized in that The dry particles A contain the following chemical components in percentage by weight: 50% to 55% silicon dioxide, 18% to 22% aluminum oxide, 0.10% to 0.35% iron oxide, 0.10% to 0.35% titanium oxide, 12% to 14% calcium oxide, 0.5% to 1% magnesium oxide, 3.5% to 4.5% potassium oxide, 2.5% to 4.5% sodium oxide, 3% to 4.5% zinc oxide, and the rest is loss on ignition.

3. The dry granular composition according to claim 1, characterized in that The dry particles B contain the following chemical components in percentage by weight: 40% to 44% silicon dioxide, 20% to 22% aluminum oxide, 0.1% to 0.35% iron oxide, 0.1% to 0.35% titanium oxide, 1.5% to 2.5% calcium oxide, 0.5% to 2% magnesium oxide, 1% to 2.5% potassium oxide, 4% to 5.5% sodium oxide, 4% to 5.5% strontium oxide, 10% to 16% barium oxide, 3% to 6% zinc oxide, and the rest is loss on ignition.

4. The dry granular composition according to claim 1, characterized in that The particle size distribution of the dry particles A satisfies: based on the total weight of the dry particles A, particles with a size of 80 to 100 meshes account for 4% to 15%, particles with a size of 100 to 160 meshes account for 22% to 30%, particles with a size of 160 to 220 meshes account for 30% to 36%, and particles with a size of more than 220 meshes account for 20% to 33%.

5. The dry granular composition according to claim 1, characterized in that The dry particles B satisfy: 10 =5~8 μm, d 50 =15~25μm, d 90 =45~55μm.

6. A ceramic tile, characterized in that: The invention comprises a dry particle layer formed by a body layer, a base glaze layer, a pattern layer, an antique protective glaze layer and the dry particle composition according to any one of claims 1 to 5 which are sequentially stacked.

7. The ceramic tile according to claim 6, characterized in that The antique protective glaze layer contains the following chemical components in weight percentage: silicon dioxide 46%~52%, aluminum oxide 17%~22%, iron oxide 0.1%~0.4%, titanium oxide 0.1%~0.3%, calcium oxide 10%~16%, magnesium oxide 1%~4%, potassium oxide 0.3%~3%, sodium oxide 1%~5%, barium oxide 0~5%, zinc oxide 2%~6%, and the rest is ignition loss.

8. The method for preparing a ceramic tile according to claim 6 or 7, characterized in that: The following steps are involved: After pressing the brick, it is dried, glazed, inkjet printed, baked, antique protective glaze applied, sprayed with dry particle suspension, fired, and edged to obtain ceramic bricks; The dry particle suspension comprises the dry particle composition as claimed in claim 1.

9. The method for preparing a ceramic tile according to claim 8, characterized in that: The dry particle suspension further comprises a suspension, wherein the dry particle composition accounts for 20 wt.% to 60 wt.% of the dry particle suspension, and the suspension accounts for 40 to 80 wt.% of the dry particle suspension.

10. The method for preparing a ceramic tile according to claim 9, characterized in that: At least one of the following conditions is met: S1. The specific gravity of the dry particle suspension is 1.0~1.35 g / mL; S2. The suspension comprises a suspending agent, wherein the suspending agent accounts for 20 wt.% to 45 wt.% of the weight of the suspension; S3. The spray-dried particle suspension satisfies: the spraying amount of the dry particle suspension is 50~150g / m 2 , spraying pressure is 4~6.5 MPa, nozzle diameter is 0.52 mm, 2~4 spray guns; S4. The baking temperature is 150 to 250 ° C, and the baking time is 0.5 to 5 min; S5. The method of applying the antique protective glaze is spraying glaze, and the following conditions are met: the specific gravity of the antique protective glaze slurry is 1.20~1.35 g / mL, and the spraying amount is 100~200 g / m 2 , spraying pressure is 4~6.5 MPa, nozzle diameter is 0.52 mm, 2~4 spray guns; S6. The sintering temperature is 1150~1165°C, and the sintering time is 35~55 min.

Citation Information

Patent Citations

  • Preparation method of antiskid and antifouling glazed tile and prepared antiskid and antifouling glazed tile

    CN111217623A

  • FFC glaze with high stain resistance, FFC sanitary ceramic and preparation method of FFC sanitary ceramic

    CN111253071A